Assessing the Garman-Kohlhagen option pricing model - Gros, Guillaume (2009)
The well-known Black Scholes model has been improved, tested by the academicians since it has seen the light of the day in 1973. Literature is much less plethoric about the Garman-Kohlhagen model (its extension to FX option valuation). This study will confront that model to the reality of FX options market. By using two sets of data representative of the most traded currency pairs on the forex, EUR / USD and EUR / GBP, we assess how it performs.